Causes of Fiscal Illusion: Lack of Information or Lack of Attention?. (June 2016) - Baekgaard, Martin; Serritzlew, Søren; Blom‐Hansen, Jens
Abstract : According to fiscal illusion theory, voters misperceive fiscal parameters because of incomplete information. The costs of public services are underestimated, implying that if voters had full information, their support for public services would drop. The literature has focused on testing the implications of fiscal illusions, whereas the question why fiscal illusions occur at all has received less attention. According to the standard argument, individuals base their opinion of policy proposals on a valuation of benefits and costs. We formalize the standard argument and show that it is a special case of the attention model of fiscal illusion. In this model, opinion depends on the saliency of attributes of the proposal. We show that the attention model can better explain fiscal illusion by deriving competing hypotheses, which are tested in a survey experiment. We conclude that the mechanism behind fiscal illusion is attention and framing, not incomplete information.